Parametric Study of Mechanical Stresses within Cement Sheath in Geothermal Wells. (February 2021) - Wu, Yuxing; Patel, Harshkumar; Salehi, Saeed
Highlights: 2D validated finite element model of casing, cement sheath, and formation Influence of two heat transferring directions. Identification of likely failure modes and locations. Effect of thermal parameters, elastic materials, and operational factors on cement integrity. Compare the sensitivity of each parameter to radial and hoop stresses. Abstract: A cement sheath, placed between the casing and the formation, is an important barrier that establishes a hydraulic seal and provides zonal isolation, preventing fluid communication in the wellbore. In geothermal wells, stress induced by high bottom-hole temperature is one of the major factors triggering failure in the cement sheath. However, the influence of heat flow direction and differential temperature, relative to other design and operating factors, is not well understood. The objective of this paper is to investigate these two important factors. In this study, an analytically verified 2D numerical model was used to perform a parametric study of mechanical stress within a cement sheath. Loading conditions applied to the model included maximum and minimum horizontal formation stresses, wellbore pressures, and temperature differences. Sensitivity analysis was conducted to understand the effect of cement properties, temperature difference between the casing and the formation, and casing pressure on stresses in the cement sheath. Sensitivity response curves demonstrated the relative influence of investigated parameters on radial and hoop stresses. Results showed that heat transfer from the formation to the casing (Ti < Tf ) is more detrimental to cement integrity than the opposite scenario (Ti > Tf ). When heat flows away from the wellbore, hoop stress in cement is mainly dependent on temperature difference, while radial stress is primarily dependent on temperature difference as well as wellbore pressure. When heat flows toward the wellbore, radial stress in cement is primarily a function of temperature difference and wellbore pressure. Hoop stress, on the other hand, is mainly dependent on temperature difference and the cement's thermal expansion coefficient.